SISTEM KONTROL BEBAN DAN MONITORING DAYA BATERAI PADA PANEL SURYA 50WP UNTUK APLIKASI PENERANGAN BERBASIS INTERNET OF THINGS - Putri, Michelin Radina; Setyawan, F. X. Arinto; Sumadi, Sumadi (Universitas Lampung, 2022)
Solar panels are the main device of a solar power generation system that functions to convert sunlight energy into electrical energy. The purpose of this study is to make it easier for users to monitor the voltage and current values in the battery generated by solar panels via smartphones with applications that have been designed, to develop tools and applications to monitor and control Internet of Things-based solar panels using the NodeMCU microcontroller so that they can be accessed via internet. The tool that will be made requires the INA219 sensor which will become one with the NodeMCU. In this study, it was found that the monocrystalline solar panel with a power of 50WP only has a de-efficiency value of 0.138%. In INA219 sensor measurement data, it can be seen that this data has a success value of 99.75% and a fairly small error value of 0.25%. On the INA219 sensor, the current value read is 0.014 to 0.712 A. This can be seen on the Blynk serial monitor.